The Effect of Individual Counseling on Assertive Training Techniques on Assertive Behavior Facing Student Bullying - Siregar, Kiki Kusnita; Nur Arjani, Nur Arjani (Medan State University, 2023)
This research aims to determine the effect of individual counseling on assertive training techniques on assertive behavior in dealing with student bullying. The research method used in this research is a quantitative method quest eksperimen . The subjects of this research were 4 students in class X-10 who had high assertive behavior scores in the face of bullying. The instrument used is to measure the scale of assertive behavior in dealing with bullying, which consists of 45 valid and reliable question items. Instruments were given before and after the implementation of individual counseling services. The data analysis technique used in this research is the Wilcoxon analysis technique with α = 0.05. The results of this research show that before (pre-test) individual counseling was carried out, the assertive training technique was 110.5 and after individual counseling was carried out, the assertive training technique was 69.5. Based on the Wilcoxon test results, we get ????ℎ????????????????g > ???????????????????????? where 5 > 0. So it can be said There is